Relationship Between Length of Surgery and Shivering in Postoperative Abdominal Surgery Patients - Yuswanto, Subur; Triyudono, Danang; Kemal Firdaus, Eza (Java Nursing Journal, 2024)
Background: Abdominal surgery is a type of major surgical operation performed in the abdominal area with incision in the wall layer. The surgery has a risk, one of which is the incidence of shivering and the long period of surgery causes a continuous process of losing body heat. Objective: to know the relationship between the length of surgery and the incidence of shivering in postoperative abdominal surgery patients in the central surgical installation of RSUD Hj. Anna Lasmanah Banjarnegara. Methods: This research design uses cross sectional. Sampling technique with total sampling obtained 50 with abdominal surgery... Instruments include age, gender, BMI, type of anesthesia, length of surgery and incidence of shevering. Findings: age with the majority of the early adult category 26-35 years at 14 (28.0%) for the majority of female gender at 35 (70%) and the highest BMI with normal at 31 (62%).The length of operation of postoperative abdominal surgery patients with the majority in the fast category less than 1 hour at 29 (58%). Conclusion: there is a relationship between the length of surgery and the incidence of shivering in abdominal surgery patients in the Central Surgical Installation of Hj. Anna Lasmanah Banjarnegara Hospital with a p_value of 0.004 (<0.05) with a relationship in the moderate category with rho 0.416 with a relationship in the moderate category with rho 0.416